Novel Mutations and Genetic Characterization in Korean Patients with Familial Renal Glucosuria - Weon Kyung Lee; Seung Hwan Oh; Woo Yeong Chung (Korean Society of Pediatric Nephrology, 2018)
Purpose Familial renal glucosuria (FRG, OMIM #233100) is a rare but relatively benign genetic condition characterized by persistent isolated glucosuria with a normal blood glucose level. We report three additional SLC5A2 mutations and examine their phenotypic and genetic characteristics in a Korean FRG cohort. We also reviewed the literature and summarized the genotypes of all Korean patients with FRG. Methods A genetic analysis was conducted by directly sequencing all 14 exons of the SLC5A2 gene and their flanking regions in six unrelated Korean children with FRG and their family members. Novel non-synonymous single-nucleotide polymorphisms were identified and compared with known mutations that are repeatedly detected in the Korean population. Results We found two novel mutations [c.274G>A (G92S) and c.1168C>T (L390F)] and one known [c.1382G>A (S461N)] mutation in each family and one recurrent mutation [c.1346G>A (G449D) (rs768392222)] in two pedigrees. The recurrent G449D was predicted to be "possibly damaging," with a score of 0.883 in Polyphen-2, while G92S, L390F, and S461N were predicted to be "probably damaging," with scores of 1.000, 0.999, and 0.996, respectively. Conclusions Two novel, one previously reported, and one recurrent mutation were identified in six Korean FRG pedigrees as causative mutations of renal glucosuria. Sequence variations in the SLC5A2 gene were frequently detected in children with persistent isolated glucosuria. A long-term follow-up of this FRG cohort is needed to understand how these specific SGLT2 mutations impair kidney function and energy homeostasis.